Resilience of the resource regions for sustainable development in Russia. (November 2021) - Filimonova, I.V.; Provornaya, I.V.; Nemov, V.Yu.; Komarova, A.V.; Dochkina, D.D.
Abstract: The economic growth of Russian regions is one of the key indicators for the country. The regional economies have significant differences in the structure of production and services, therefore, ensuring economic growth depends on various factors of the internal structure and external influence. In this regard, the task of searching for growth factors and risk factors for the sustainable development of Russian regions becomes important. The aim of this work is to assess the resilience of the economy of energy resource regions of Russia to changes in the fiscal energy policy of the state. The authors found that such factors exert the strongest influence as tax yield and the balance of tax payments. Moreover, the energy resource regions of Russia are resilient to these factors. Considering the tax security of the regional budget, we can say that it has a fairly strong impact. The regional budget deficit and the level of budgetary provision have little impact on the economic growth of oil-producing regions. From which the authors conclude that the energy regions are resilient to these factors. The regional budget deficit has the smallest impact. After division into clusters, it was revealed that the main oil-producing regions of Russia turned out to be resilient to changes in the fiscal energy policy of the state. Only eight regions of the considered ones turned out to be resilient: Krasnoyarsk Krai, Tyumen Oblast, Astrakhan Oblast, Republic of Sakha, Kaliningrad Oblast, Sakhalin Oblast, Novosibirsk Oblast and Omsk Oblast.